INSTILLING AND STRENGTHENING THE CONSCIOUSNESS OF YOUNG PEOPLE TO ENSURE INFORMATION SECURİTY - Sultonov To’lqin Azamatovoch; Abdumalikova Odinaxon (American Journals Publishing, 2024)
Ability to use modern information technologies; communication with the artificial intelligence system, dialogic communication in the "hybrid intelligence" man-machine system, telematics tools, processes of using global and local information and computing networks were studied.
Keywords: Information, know-how, hybrid intellect, information retrieval culture, “Information scarcity”, state, society, management, civil service, civil servant, competence, model, components, evaluation, stages.